Pengembangan Desa Peduli Lingkungan di Desa Ngalang Gedangsari Gunungkidul - Mulasari, Surahma Asti; Andrianty, Athika Ayu; Az Zahra, Zharifatul Ulya; Alhanani, Syahrul Akbar; Djamil, Setia Nanda Nabila; Nafiati, Lu'lu' Asti; Yuliansyah, Herman Asti; Tentama, Fatwa Asti; Sulistyawati, Sulistyawati; Sukesi, Tri Wahyuni (CV. Rayyan Dwi Bharata, 2025)
This community service activity aims to develop an environmentally conscious village (Desa Peduli Lingkungan) in Ngalang Village, Gedangsari, Gunungkidul, through the introduction and implementation of sustainable waste and resource management practices. The program focused on four key interventions: (1) utilization of maggot (Hermetia illucens) as an alternative feed for catfish to reduce feed costs and enhance growth, (2) application of stacked bucket systems for household organic waste composting to produce liquid organic fertilizer, (3) education on the importance and development of domestic wastewater drainage systems (SPAL), and (4) household waste management using the 3R approach (Reduce, Reuse, Recycle). The method involved educational sessions, distribution of pamphlets, pre- and post-tests to assess knowledge improvement, and practical demonstrations. Results showed significant increases in participants’ knowledge and skills across all topics, supported by strong engagement from community members and students involved in the KKN program. These integrated actions promote environmental awareness, support food security, and foster community empowerment using locally appropriate and sustainable technologies.Keywords: maggot, compost, wastewater, waste management, community empowerment